2014
DOI: 10.3807/josk.2014.18.1.045
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Properties of BaSi2O5:Eu2+Phosphor Film Fabricated by Spin-Coating of Ba-Eu Precursor on SiO2Glass

Abstract: Well-crystallized BaSi2O5:Eu2+ phosphor films were synthesized by heat treatment of spin-coated BaO:Eu on SiO2 glass. We investigated luminescence-structure properties of these phosphor films as a function of heat-treatment temperature. From x-ray diffraction patterns, our BaSi2O5:Eu 2+ phosphor films revealed that (111)-and (204)-crystal planes of BaSi2O5 crystal were dominantly increased with an increase of heat-treatment temperature. Photoluminescence intensities of BaSi2O5:Eu 2+ phosphor films were increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Barium silicates are extensively studied for their excellent material properties and device performance in a range of important technological applications [1][2][3][4][5][6][7] Sanbornite (low-BaSi2O5) is a uncommon mineral found in Big Creek, California (USA), and its hydrous analogue bigcreekite (BaSi2O5•4H2O) are rare examples where Ba is concentrated in a silicate phase [8][9][10]. On the other hand, Ba5Si8O21 is a synthetic phase, displaying the rare characteristic of being an anhydrous phase containing ribbons (quadruple zweier chains) of silica tetrahedra surrounded by Ba cations which stabilize the stretched chains.…”
Section: Introductionmentioning
confidence: 99%
“…Barium silicates are extensively studied for their excellent material properties and device performance in a range of important technological applications [1][2][3][4][5][6][7] Sanbornite (low-BaSi2O5) is a uncommon mineral found in Big Creek, California (USA), and its hydrous analogue bigcreekite (BaSi2O5•4H2O) are rare examples where Ba is concentrated in a silicate phase [8][9][10]. On the other hand, Ba5Si8O21 is a synthetic phase, displaying the rare characteristic of being an anhydrous phase containing ribbons (quadruple zweier chains) of silica tetrahedra surrounded by Ba cations which stabilize the stretched chains.…”
Section: Introductionmentioning
confidence: 99%
“…Finally the ZnO film was annealed at 450℃ for 2 h in a furnace. Since all steps of coating (adsorption, reaction, and rinsing) take place simultaneously during spin coating, this method does not require any rinsing step for elimination of residual organic materials [48]. The mean thickness of the ZnO film was about 70 nm.…”
Section: Deposition Of Zno Seed Layermentioning
confidence: 99%
“…Disordering is replaced by ordering in a crystallized part of the material, so crystalline field, distribution of the local charge compensation in the vicinity of activator as well, are changed. For instance, recent study of europium doped barium disilicate glass system showed that luminescent properties of the material are strongly affected by crystallization [4,5]. Eu 2+ -ions luminescence, which was not detected in a mother glass, became dominating when glass material was crystallized by thermal treatment.…”
Section: Introductionmentioning
confidence: 98%